Bartonella henselae infection in a dog with recalcitrant ineffective erythropoiesis. (2nd February 2018) - Randell, Martin G.; Balakrishnan, Nandhakumar; Gunn‐Christie, Rebekah; Mackin, Andrew; Breitschwerdt, Edward B.
Abstract: Ineffective erythropoiesis was diagnosed in an 8‐year‐old male castrated Labrador Retriever. Despite treatment with immunosuppressive therapy for suspected immune‐mediated erythrocyte maturation arrest, resolution of the nonregenerative anemia was not achieved. Following documentation of Bartonella henselae bacteremia by Bartonella alpha proteobacteria growth medium (BAPGM) enrichment blood culture, immunosuppressive therapy was discontinued, and the anemia resolved following prolonged antibiotic therapy. Bartonella immunofluorescent antibody testing was negative, whereas B henselae western blot was consistently positive. The contribution of B henselae bacteremia to ineffective erythropoiesis remains unknown; however, the potential role of B henselae in the pathophysiology of bone marrow dyscrasias warrants additional investigation.